Effect of differing feedstock and operational conditions on properties of biochar - Koh, Nicholas Teck Chuen (Nanyang Technological University, 2024)
Pyrolysis process is attracting attention in the field of treating and recycling organic waste due to the advantages of large volume of waste reduction and biochar production. The product of biochar holds significant promise and importance across various fields because of its unique properties and potential applications. It is known that the application of biochar in multiple different aspects depends on the properties of biochar products. The feedstocks and pyrolysis conditions, especially pyrolytic temperature are the key factors affecting the quality of biochar product. Most previous studies have only involved one or two specific feedstocks for biochar production. The quality of biochar would differ when feedstock materials of different composition are utilized. The relationships between different feedstocks, operational conditions and biochar properties have not been comprehensively investigated. Thus, it is essential to optimize the biochar production conditions and explore the impact of different feedstocks to biochar product. In this project, four types of feedstocks (including thermally hydrolysed anaerobic sludge, co-digestion sludge with food waste, food waste and plant waste) were pyrolyzed into biochar at varying pyrolytic temperature from 300 to 600 oC, to study the effect of different feedstocks and different pyrolysis conditions to the properties of biochar products. The properties of biochar composition, surface area, functional groups and heating values were characterized. It was observed that THP-AD sludge had the highest sludge yield as well as surface area and pore volume. Meanwhile, through the analysis of FTIR, functional groups like -OH was formed after higher temperature pyrolysis. These findings indicate the potential of using THP-AD sludge biochar as adsorbents for contaminant removal. In addition, food waste at 300 °C had the highest heating values of close to 27000 J/g, which is comparable to common fuel standards such as coal with a higher heating value of about 24000J/g. This implies the possibility of using food waste biochar as an alternative fuel. The linear equation was found between the feedstock elemental compositions (%) and their respective heating values(J/g): HHV = 340.72C + 966.10H – 45.27N + 420.72S - 414.88. Such insights could lead to the development of biochar products with enhanced performance for specific applications, such as wastewater treatment, pollutant removal and alternative fuels.